Endurance assessment in handball: a systematic review - Camacho-Cardenosa, A.; Camacho-Cardenosa, M.; Brazo-Sayavera, J. (European Journal of Human Movement, 2019)
Introduction: recent research has shown that although training stimuli for high-intensity endurance training should be given more attention in the full handball training season planning, a high aerobic capacity appears to be important to maintain a high level of performance over the 60 minutes of playing time. In spite of there are many different tests to evaluate endurance in this way, these are used without clear logic, independently of age, level or gender. Reviewing in the current literature the endurance test carried out in the handball sport could be the first step to clarify this problem. Methods: articles published between 2002 and 2019 in PubMed, Web of Science and SPORT Discuss, in English or Spanish languages, observational and experimental studies that evaluated endurance outcomes in handball players of any age were selected. Results: 50 studies measured anaerobic efficiency and 63 studies measured aerobic efficiency, involved 3,649 handball players of different age categories. Conclusions: a great variety of studies have shown the importance to choose field-specific tests to assess anaerobic and aerobic efficiency, being shuttle RSA tests and Yo-Yo IR1 test the most reliable and used test in this sense.